Havoc : a novel - Bollen, Christopher, 1975- (Harper, an imprint of HarperCollins Publishers, 2024)
"A fast-paced literary thriller for fans of The Bad Seed, set in a crumbling luxury hotel in Egypt, in which an elderly widow and an 8 year old boy find themselves rivals, locked in a gleefully criminal psychological game of cat-and-mouse"--